DIVERSITY ASSESSMENT OF FUNGAL COMMUNITIES ASSOCIATED WITH LEAF BLIGHT DISEASE OF MAIZE (Zea mays) AND PURPLE BLOTCH DISEASE OF ONION (Allium cepa) IN SAMARU, ZARIA, NIGERIA - Adullahi, Abba Khalid; Abdullahi, Alhaqqatu (FUDMA Journal of Sciences, 2026)
Leaf blight of maize and purple blotch of onion are economically important foliar diseases that significantly reduce crop yield and quality in tropical and subtropical agro-ecosystems. This study comparatively investigated the fungal communities associated with leaf blight symptoms of maize (Zea mays L.) and purple blotch symptoms of onion (Allium cepa L.) in Samaru, Zaria, Nigeria. Diseased leaf samples were collected from farmers’ fields and analyzed using standard mycological techniques. Fungal isolates were cultured on Potato Dextrose Agar (PDA) supplemented with chloramphenicol and identified based on macroscopic and microscopic characteristics. The frequency of occurrence of each fungal genus was determined, and diversity indices were calculated to assess community structure. Three fungal genera were isolated from maize: Helminthosporium, Colletotrichum, and Fusarium, while onion samples yielded Alternaria, Botrytis, and Fusarium. Fusarium was the only genus common to both crops. The Jaccard similarity index (0.20) indicated low similarity between the fungal communities, despite the similarity in disease symptoms. Shannon diversity indices revealed moderate and comparable fungal diversity in both crops. Molecular identification and pathogenicity assays are recommended to confirm the causal roles of the isolated fungi and improve disease management strategies.
Keywords: Zea mays; Allium cepa; purple blotch; fungal diversity; Jaccard similarity; Nigeria